Interpretasi Sistem Perpustakaan Sekolah Dasar Berbasis Web - Pratiwi, Emy Yunita Rahma; Ahmad, Masitah; Siswanto, M. Bambang Edi; Rochmania, Desty Dwi; Salamah, Evi Rizqi; Dwinata, Anggara (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
This study interprets the role of web-based school digital libraries in supporting elementary school students' reading interests. This study was conducted at SD Plus Darul Ulum Jombang as one of the leading schools that has implemented web-based digital libraries as an effective reading medium for students. The research approach used was a qualitative study with a narrative study design. The results of the study indicate that the operation of web-based school digital libraries has been carried out well in supporting students' reading and literacy interests. The level of student reading interest is influenced by aspects of enthusiasm, content preferences, and variations of reading books read. The challenges and limitations of web-based digital libraries lie only in technology access and students' digital skills in understanding the features on the library web. The implications of the study are expected to be a strategy for elementary school institutions in implementing web-based digital libraries as a form of supporting student reading and literacy services by integrating with technological developments.